Strategi Penanggulangan Kemiskinan Daerah Kabupaten Kediri - Susilo (Jurnal Aplikasi Manajemen, 2009)
Poverty is a very complexity problem, that causes by intern factor (individual, family, or community) and extern factor (social, politic, law and economic condition). Because of that, government must to concern to ward off it by means of (poverty reduction strategy paper-PRSP). PRSP considered that poverty as a multidimention problems, it means tackling of poverty act through all aspect. To arrange PRSP, researcher use descriptive method with analysis-descriptive design. It give sketch the relationship of phenomenons poverty in Kediri residence. From the result, can make inspection, arrange point of view and mission, policy and strategy to ward off of poverty.